Islamic Religious Paradigm: Human Nature of Abdul Muhaimin for the Basic of Audit Philosophy - Irfan, Andi; Triyuwono, Iwan; Djamhuri , Ali; Mulawarman , Aji Dedi (Accounting Department,, 2024)
Purpose — This article aims to present a new Islamic religionist paradigm that explores the foundations of the auditing philosophy. Design/methodology/approach—The study's research method utilizes revelation, reason and senses, intuition, and interpretation. This article uses the tadabbur interpretation method. Findings—Islam guarantees human activities following His commands. Science developed from the Creator, who knows everything in the universe. Abdul Muhaimin’s human nature is defined as a “Servant of Allah who is supervised, able to say and testify about Haq (truth), trustworthy and responsible to Allah SWT for all actions in this world. This describes the figure of an auditor and becomes the basis of audit philosophy.